Recognition as a Philosophical Practice: From "Warring" Attitudes to Cooperative Projects. Issue 1 (2nd January 2021) - Bankovsky, Miriam
ABSTRACT: What does it mean to practice a theory of recognition within the discipline of philosophy? Across an initially acrimonious French-German divide, Axel Honneth's effort to recognise the value of contemporary French philosophy and social theory suggests that philosophy is a self-critical, outwardly oriented, and cooperative discipline. First, mobilising the idea of recognition in his own philosophical practise has permitted Honneth to notice non-deliberative aspects of social interaction that Habermas had overlooked, including the need for self-confidence (drawn from a "deconstructive" ethics of care) and the need for self-esteem (informed by Sartre's and Foucault's attention to the existential damage caused by denigration, and the nefarious effects of reproductive power). Second, although Honneth's ascription of value to contemporary French theory also involves mis-recognition, his practice of recognition has nonetheless prompted philosophical cooperation among theorists who would not otherwise have engaged, encouraging French-influenced critical theorists to extend Honneth's theory in ways that he had not anticipated. What emerges is an interpretation of philosophy as an ongoing intersubjective pursuit that attempts to respond to its own limitations through cooperative critique.